Perspective of Islamic Religious Education Values in the Tradition of Sea Alms in Kedung Village, Malang - Ajib Dakiroh; Ali As'ad (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This study discusses how the values of Islamic religious education are in the tradition of sea alms. This study aims to describe the values of Islamic Religious Education (PAI) contained in the sea alms tradition in Kedung Malang Village, Kedung District, Jepara Regency. Although this practice contains religious and worship values that should be taught to the community, it is often considered contrary to Islamic teachings. Therefore, this study also focuses on how instilling these values can improve people's understanding of religion. The methodology used in this study is qualitative research with a phenomenological approach. The focus of this study is on the residents of Kedung Malang Village, especially religious leaders and fishermen. To identify information, data collection was carried out through documentation, interviews, and observations. Data analysis was carried out using an interactive model from Miles, Huberman, and Saldana, which includes data reduction, data condensation, data presentation, and conclusion. The results of the study indicate that the sea alms tradition not only reflects local culture, but also contains strong PAI values, including social concern, interpersonal cooperation, and gratitude to God. The instillation of moral principles and character in society, especially among youth and the younger generation, can also be done through this tradition. Thus, this study provides insight into the importance of integrating religious values into local cultural practices that can strengthen the understanding and practice of Islamic teachings in society